Desain Pendidikan Multikultural pada Pendidikan Dasar - Hardian Mei Fajri; Arifin Maksum; Arita Marini (Universitas Negeri Padang, 2024)
The purpose of this research is to integrate and construct the design of multicultural education in basic education. This research is a descriptive qualitative research with a literature study approach. The data collection technique is done through the documentation method of journals, articles, and books related to multicultural education. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The result of this research is the interpretation of the theoretical basis of multicultural education design in basic education which includes various: (1) Definition of Multicultural Education; (2) Principles of Multicultural Education; (3) Multicultural Education Procedures; (4) Multicultural Education Approaches; (5) Multicultural Education Models; (6) Integration of Multicultural Education in the Curriculum through Religious Education, Pancasila and Citizenship Education (PPKn), Social Sciences (IPS), School Programs, and Local Content.